Fundamentals of database systems - Elmasri, Ramez; Navathe, Shamkant B. (Pearson Addison Wesley, 2007)
This edition combines clear explanations of database theory and design with up-to-date coverage of models and real systems. It features excellent examples and access to Addison Wesley's database Web site that includes further teaching, tutorials and many useful student resources.